Use Of Criminal Investigation Scientific Method In Crime Investigation: (Case Study in South Sulawesi Police) - Farah Syah Reza (VRISPRAAK : International Journal of Law, 2024)
Implementation of the use of methods scientific criminal investigation (SCIM) by the holder of the legal authority to take action to investigation in uncovering a criminal act and an attempt to find the culprit is a scientific approach to the implementation of the inquiry and investigation that can be used by police investigators in general and investigators in the ranks of the Police Sulawesi Police South in carrying out its functions and authority in the field of criminal investigation that occurred in their jurisdiction. This approach is a scientific approach to the functioning of the technology as an effort of finding evidence of transparent and accountable in the investigation of a crime. This method is seen as a solution or answer to the various modes of crimes using technological means.